Comparison of Antinociceptive Properties Between Sevoflurane and Desflurane Using Pupillary Dilation Reflex Under Equivalent Minimum Alveolar Concentration: A Randomized Controlled Trial. (12th May 2022) - Kim, Soo Yeon; Kim, Ji-Yoon; Kim, Jonghae; Yu, Seungcheol; Lee, Kwang Hyun; Lee, Hyeon Seok; Oh, Min Seok; Kim, Eugene
Abstract : BACKGROUND: The pupillary dilation reflex (PDR), the change in pupil size after a nociceptive stimulus, has been used to assess antinociception during anesthesia. The aim of this study was to compare the antinociceptive properties of sevoflurane and desflurane by measuring the PDR amplitude. METHODS: Seventy patients between 20 and 55 years of age were randomly allocated to receive either sevoflurane or desflurane. The PDR amplitude after an electrical standardized noxious stimulation (SNT) was measured using an infrared pupillometer under 1.0 minimum alveolar concentration (MAC). The pupil diameter was measured from 5 seconds before to 5 minutes after the SNT. The mean arterial pressure (MAP), heart rate (HR), and bispectral index (BIS) were also measured immediately before and after SNT as well as 1 minute and 5 minutes after SNT. The primary outcome was the maximum percent increase from the prestimulation value of the pupil diameter, and the secondary outcomes were the maximum percent increase from the prestimulation value of the MAP, HR, and BIS after SNT. RESULTS: The maximum percent increase of the pupil diameter after SNT was not different between the 2 groups (median [first quartile to third quartile], 45.1 [29.3–80.3] vs 43.4 [27.0–103.1]; median difference, −0.3 [95% confidence interval, −16.0 to 16.5]; P = .986). Before SNT, the MAP was higher under 1.0 MAC of sevoflurane than desflurane; however, the maximum percent increase of MAP, HR, and BIS was not different between the 2 groups. CONCLUSIONS: The amount of change in the PDR amplitude, MAP, and HR after SNT was not different between sevoflurane and desflurane anesthesia. This result might suggest that sevoflurane and desflurane may not have different antinociceptive properties at equivalent MAC.